WORK-RELATED COGNITIVE RESERVE PREDICTS COGNITIVE FUNCTIONING AND DEPRESSION IN OLDER ADULTS - Šneidere, Kristīne; Ozoliņa, Zane; Stepens, Ainārs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In the past decade, there has been a rapid increase in people aged over 65 – in Latvia, it constitutes 34% of the population. It has been well established that depression is one of the psychiatric diseases often comorbid to dementia, therefore it is important to identify life-style related factors that could contribute not only to the delay of dementia symptoms but also decrease the possibility of depression in older adults. Thus the study aimed to investigate the relationship between work-related cognitive reserve, depression and overall cognitive functioning in older adults with no diagnosis of dementia or depression.84 older adults aged from 65 – 92 (Mdn = 77, SD = 6.17, 76% women) with no diagnosis of dementia or depression participated in the study. To assess work-related cognitive reserve, Cognitive Reserve Index questionnaire (Nucci, Mapelli, & Mondini, 2012) was used, while for depression measures the 15- item Geriatric Depression Scale (Sheikh & Yesavage, 1986) was used. Overall cognitive functioning was measured using The Montreal Cognitive Assessment scale (Nasreddine et al., 2015).To identify the relationship between the three variables, Spearman correlation coefficient was used. All variables correlated significantly. Both, work-related cognitive reserve and depression, predicted cognitive functioning. These results offer an insight into the possible positive contribution of the cognitive reserve not only to cognitive functioning, but also psychological well-being later in life. More studies in larger samples should be conducted to confirm the observation from this study.